Transient liquid phase bonding of IC10 single crystal with GH3039 superalloy using BNi2 interlayer: Microstructure and mechanical properties. (15th January 2016) - Zhang, L.X.; Sun, Z.; Xue, Q.; Lei, M.; Tian, X.Y.
Abstract: Transient liquid bonding (TLP) of IC10 single crystal with GH3039 alloy was carried out using BNi2 interlayer. Microstructure evolution and mechanical properties of the joints bonded at 1050–1200 °C for 2 h were investigated. The precipitates in the DZ on the GH3039 side gradually decreased and disappeared with the increase of the bonding temperature. The formation mechanism of the TLP joint was proposed and the asymmetry of the bonding was discussed. Tensile strength and microhardness tests were conducted to investigate the mechanical properties of the joints. The layer of borides with high hardness in the joint bonded at 1150 °C significantly reduced the room-temperature tensile strength but had little effect on the high-temperature tensile strength of the joint. The layer of borides became the preferential position to crack during both room-temperature and high-temperature tensile tests. The joints with dispersive precipitates had the highest room-temperature tensile strength and the homogenized joints showed the best ductility. Graphical abstract: Highlights: IC10 single crystal and GH3039 superalloy are bonded using TLP method. Effect of temperature on joint microstructure and mechanical properties is investigated. A layer of continuous borides could reduce room-temperature tensile strength of the joint. Borides could reduce the high-temperature elongation of the joint. The formation mechanism of the TLP joint is proposed in this paper.